A CONTRASTIVE STUDY OF WORDS OF PRAISE IN ENGLISH AND UZBEK LANGUAGES - Norkobilova Nigora Uralovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. this article explores the linguistic and cultural features of words of praise in english and uzbek languages. words of praise serve as a universal means of expressing admiration, encouragement, and approval. however, their linguistic realization and pragmatic functions differ according to cultural traditions. the research highlights the structural, semantic, and pragmatic characteristics of praise expressions, emphasizing how national mentality and social norms shape their usage in both languages.